The engineering challenges in quantum computing - Almudever, C. G.; Lao, L.; Fu, X.; Khammassi, N.; Ashraf, I.; Iorga, D.; Varsamopoulos, S.; Wallraff, A.; Geck, L.; Kruth, A.; Knoch, J.; Bluhm, H.; et al. (Proceedings of the 2017 Design, Automation and Test in Europe, DATE 2017, 2017)
Quantum computers may revolutionize the field of computation by solving some complex problems that are intractable even for the most powerful current supercomputers. This paper first introduces the basic concepts of quantum computing and describes what the required layers are for building a quantum system. Thereafter, it discusses the different engineering challenges when building a quantum computer ranging from the core qubit technology, the control electronics, to the microarchitecture for the execution of quantum circuits and efficient quantum error correction. We conclude by discussing some compiler and programming issues relative to quantum algorithms.
CRIS-Team Scopus Importer:2022-06-27
Keywords: Quantum computing; Logic gates; Computers; Buildings; Error analysis; Quantum entanglement; Error correction